Effect of Achyranthes Aspera Linn. Leaves Extract on Reactive Oxygen Species (ROS) in Diabetes-induced Rats by Flow cytometry and Possible Molecular Mechanism through Molecular Docking - Deshpande, Trupti C.; Une, Hemant D. (Current Enzyme Inhibition, 2021)
Background: Oxidative stress is caused due to the overproduction of the reactive oxygen species (ROS) and the disturbance developed in the antioxidant potential of biochemical processes. ROS mostly form in the brain due to the high consumption of oxygen and the insufficiency of endogenous antioxidant resistance mechanisms. Cytochrome P450 2E1 has an excessive percentage of NADPH oxidase activity, which causes the production of ROS and increases oxidative stress. Objectives: We have studied the effect of ethyl acetate extract of Achyranthes Aspera (EAAA) on ROS in the brain of diabetes-induced rats. We have also investigated the possible molecular mechanism of reduction in ROS through molecular docking. Methods: To study the oxidative stress induced by ROS in diabetic rats, we estimated the ROS in rat brain through flow cytometry. The oral dose of EAAA 50mg/kg and 100 mg/kg was given to diabetesinduced rats. Results were articulated as mean ± standard deviation (SD). Data were analyzed using analysis of variance (ANOVA) followed by Bonferroni as a post hoc test. We performed molecular docking of flavonoids on CYP2E1 to study the inhibitory potential. Results: The results have shown that EAAA reduces the generation of ROS in the diabetes-induced rat in a dose-dependent manner. The oral dose of EAAA 50mg/kg and 100 mg/kg was given to the rats and the ROS generation got affected accordingly. Luteolin, quercetin, and apigenin inhibited the CYP2E1 very effectively. Luteolin formed 4 hydrogen bonds with CYP2E1, which indicated its potential inhibition. Although, luteolin and apigenin showed a very good binding affinity with the enzyme. Conclusion: From the present work, we have concluded that the ethyl acetate extract of achyrantesaspera can effectively inhibit the ROS generation in the diabetes-induced rats by inhibiting the activity of CYP2E1.
Keywords: CYP2E1